Intellectual capital in small and medium enterprises; case study of Malaysian manufacturing SMES - Othman, Masayu; Saud, Mohammad Basir (2015)
Intellectual capital is used by the SMEs to survive in the competitive market as well as maintain their performance.This study intends to identify the influence of intellectual capital on SMEs in Malaysia and the way that contributes in the performance of the overall organization. This paper also aims to examine whether SMEs organizations in Malaysia are using IC or not. The finding of this study indicated a positive relationship between intellectual capital and SMEs organizational performance in Peninsular Malaysia. This study associated the lack of SMEs organizational performance in Malaysia into the lack of intellectual capital.The finding of this study helps to better understanding SMEs performance in Malaysia and highlights the intensity of strategic or business orientation as the key solution to the lack of organizational performance.In this respect, Malaysian SMEs organizations should adopt techniques of intellectual capital as a primary condition to the success of their organizations.